Efeito da exposição aguda à fumonisina B1 nas convulsões induzidas por pentilenotetrazol em camundongos - Poersch, Alice Bertotto (2014)
Mycotoxins are secondary metabolites, produced by fungi species of the genus Aspergillus, Fusarium, Penicillium and Claviceps. The high incidence of toxicity is by ingestion of contaminated plant products and by consuming products derived from food. Among the 400 different mycotoxins; there are the fumonisins, especially fumonisin B1 (FB1), which corresponds to about 70% of total fumonisins. It has been demonstrated that toxicity of this mycotoxin may be related to toxic effects on the central nervous system, engaging in inflammatory processes and seizures. The mechanism of toxicity of fumonisins is related to the metabolism of sphingolipids in which the breakdown of these sphingolipids complexes and accumulation of sphingoid bases alter important cellular functions, favoring oxidative stress, inhibition of protein secondary and excitotoxicity. Thus, this work tried to investigate whether FB1 is able to enhance the inductive effect of the model of pentylenetetrazole (PTZ) seizures. We also evaluated the mechanism of action responsible for this effect, in order to study strategies that make it possible to prevent or minimize their toxic effects. So, C57BL/6 mice were exposed to FB1 (8 mg/kg i.p.) or vehicle (1.6% DMSO + 0.9% NaCl i.p.) and elapsed 30 minutes were injected with PTZ (30 mg/kg i.p.) or vehicle (0,9% NaCl i.p.). Behind 15 minutes observation, mice were euthanized and cerebral cortex and hippocampus were collected for analysis of Na+, K+-ATPase activity, membrane potential and mitochondrial complex I and II activities. FB1 reduced latency for myoclonic jerks and increased myoclonus number. Even, Na+, K+-ATPase total activity as well as subunit 1of this enzyme were increased in cerebral cortex of animals treated with FB1, but in hippocampus it was reduced. FB1 elevated mitochondrial membrane potential in cerebral cortex however mitochondrial complex I and II activity weren t changed in both structures with this treatment. PTZ was able to enhance Na+, K+-ATPase 2/3 subunit activity in hippocampus. Thus, we showed that FB1 induces neurotoxicity, since this mycotoxin FB1 facilitates seizures induced by PTZ, altered mitochondrial membrane potential and the enzyme Na+, K+ - ATPase activity, which are possibly mediating the mechanism of toxicity.